No Effect of a Self-Help Book for Insomnia in Patients With Obstructive Sleep Apnea and Comorbid Chronic Insomnia – A Randomized Controlled Trial - Bjorvatn, Bjørn; Berge, Thomas; Lehmann, Sverre; Pallesen, Ståle; Saxvig, Ingvild W. (Frontiers in Psychology, 2018)
Objective: To compare the effects of a self-help book for insomnia to that of sleep hygiene advice in a randomized controlled trial with follow-up after about three months among patients who were diagnosed with obstructive sleep apnea (OSA) and comorbid chronic insomnia, and who were concurrently initiating treatment with continuous positive airway pressure (CPAP). Method: In all, 164 patients were included. OSA was diagnosed and categorized based on a standard respiratory polygraphic sleep study using a type 3 portable monitor. The self-help book focused on cognitive behavioural therapy for insomnia. The main outcome measure was insomnia severity assessed with the Bergen Insomnia Scale (BIS) and the Insomnia Severity Index (ISI). Results: Significant improvement on the BIS and the ISI was seen from pre-treatment to follow-up in both conditions; sleep hygiene advice (26.8 vs. 21.8, p<0.0005 and 17.0 vs. 14.1, p<0.0005, respectively) and self-help book (26.3 vs. 22.4, p<0.0005 and 16.6 vs. 13.6, p<0.0005, respectively). No time x condition interaction effects were detected, suggesting that the self-help book did not improve insomnia symptoms more than the sleep hygiene advice. Conclusions: In this randomized controlled trial among patients with OSA and comorbid insomnia who were initiating CPAP treatment, concurrently treating their insomnia with a self-help book did not improve sleep more than sleep hygiene advice. The improved sleep at follow-up in both groups is most likely explained by the CPAP treatment.